2022
DOI: 10.1149/1945-7111/ac5cf2
|View full text |Cite
|
Sign up to set email alerts
|

State of Charge Estimation for Lithium-Ion Batteries Based on TCN-LSTM Neural Networks

Abstract: Accurately estimating the state of charge (SOC) of lithium-ion batteries is critical for developing more reliable and efficient electric vehicles. However, the commonly used models cannot simultaneously extract effective spatial and temporal features from the original data, leading to an inefficient SOC estimation. This paper proposes a novel neural network method for accurate and robust battery SOC estimation, which incorporates the temporal convolutional network (TCN) and the long short-term memory (LSTM), n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Experimental findings revealed that the proposed TCN-based SOH estimation model exhibited high accuracy in estimation and demonstrated good adaptability across different battery types. 18 Wen proposed a model based on incremental capacity analysis and BP neural network to predict battery SOH at different ambient temperatures. By analyzing the correlation between IC curve characteristics and SOH, the mapping relationship between temperature and IC curve characteristics was established by the least square method, and the SOH prediction model at different temperatures was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental findings revealed that the proposed TCN-based SOH estimation model exhibited high accuracy in estimation and demonstrated good adaptability across different battery types. 18 Wen proposed a model based on incremental capacity analysis and BP neural network to predict battery SOH at different ambient temperatures. By analyzing the correlation between IC curve characteristics and SOH, the mapping relationship between temperature and IC curve characteristics was established by the least square method, and the SOH prediction model at different temperatures was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Using a Genetic Algorithm (GA) to search for the smoothing time interval for the optimal ERTSS, various dynamic unit tests were performed. Reference (Hu et al, 2022) extracts higher-level spatial features between multi variables into the current SOC and historical input, to achieve state assessment. However, the above-mentioned methods have low accuracy and large errors, so they cannot be accurately evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…during battery operation as inputs. [18][19][20][21][22] Ref. [23] proposed an improved feedforward-long short-term memory (FF-LSTM) modeling method to realize an accurate whole-life-cycle SOC prediction by effectively considering the current, voltage, and temperature variations.…”
mentioning
confidence: 99%